Treatment‐related reductions in catastrophizing predict return to work in individuals with post‐traumatic stress disorder. Issue 1 (15th March 2017) - Sullivan, Michael; Adams, Heather; Ellis, Tamra; Clark, Robyn; Sully, Craig; Thibault, Pascal
Abstract: Post‐traumatic stress disorder (PTSD) has been associated with high rates of work‐disability. In other domains of research, it has been shown that catastrophic thinking also contributes to work‐disability. The present study examined the relation between catastrophic thinking and work‐disability in individuals with PTSD. The study sample consisted of 73 work‐disabled individuals with PTSD who were referred to an occupational rehabilitation service. Participants completed measures of post‐traumatic stress symptoms, depression, pain, catastrophic thinking, and occupational disability at admission and termination of the rehabilitation intervention. Return‐to‐work was assessed 1 month following the termination of the rehabilitation intervention. Cross‐sectional analyses revealed that catastrophic thinking contributed significant unique variance to the prediction of occupational disability, even when controlling for the severity of symptoms of PTSD. Prospective analyses revealed that treatment‐related reductions in catastrophic thinking predicted successful return to work, beyond the variance accounted for by reductions in the severity of symptoms of PTSD. The findings suggest that catastrophic thinking is a determinant of occupational disability in individuals with PTSD. The findings further suggest that interventions designed to reduce catastrophic thinking might promote more successful occupational re‐integration in individuals recovering from post‐traumatic stress symptoms.